Violet glasses… but with what lenses? Theoretical routes between the production and the reproduction of work - Andreina Colombo (Íconos)
The present article intends to engage in a discussion around the concept of work (or works) from a gendered perspective. Special attention will be given to the relationship between the realms of production and those of reproduction. The goal of this reading is to establish the most important variations between the two, underlining the differences and similarities between the diverse conceptual approaches in use. Using the analogy of the “purple glasses”, three different approaches are identified: (i) with single vision lenses (looking at either production or reproduction), which attempts to describe the two realms from the viewpoint of only one of the two, ii) with bifocal lenses, which consider productive and reproductive work as equally relevant, while establishing clear-cut differences between the two, and iii) with progressive lenses, which allow us to see the two domains as part of a continuum, stressing their simultaneities, overlays and intermittencies . Taking into account the proliferation of studies espousing a gender perspective – and without denying their peculiar contributions- , the approach attempted here tries to determine how each “lens” is useful in efforts to grasp the particular patterning of each kind of work and to supplement such analysis by taking into account specific times and places.